The chemistry of light and photography in their application to art, science, and industry - Vogel, Hermann Wilhelm 1834-1898 (Cambridge University Press, 2011)
First published in 1875, this book describes the history & science of photography, with an emphasis on the practical processes involved and their relation to the physical & chemical properties of light. Hermann Vogel, who pioneered the technology for colour photography, was Professor of Photography at the Royal Industrial Academy of Berlin. Here he explains the science of photography simply & concisely for a popular readership. The book has 100 illustrations, including both woodcuts & 'specimens of the latest discoveries in photography', intended to demonstrate the value of the technology to society. It traces the history of photography from its beginnings in experiments conducted by Davy & Wedgwood & the invention of the Daguerreotype to the most recent developments of Vogel's day. It was regarded as the most comprehensive guide to photography then available, & ran to several editions.